Automatic speech signal segmentation based on the innovation adaptive filter - Makowski, Ryszard; Hossa, Robert (Zielona Góra: Uniwersytet Zielonogórski)
Speech segmentation is an essential stage in designing automatic speech recognition systems and one can find several algorithms proposed in the literature. It is a difficult problem, as speech is immensely variable. The aim of the authors` studies was to design an algorithm that could be employed at the stage of automatic speech recognition. This would make it possible to avoid some problems related to speech signal parametrization.
Keywords: automatic speech segmentation; inter-phoneme boundaries; Schur adaptive filtering; detection threshold determination